Lipid Peroxidation in Colorectal Carcinogenesis: Bad and Good News - Pizzimenti, Stefania; Toaldo, Cristina; Pettazzoni, Piergiorgio; Ciamporcero, Eric; Dianzani, Mario Umberto; Barrera, Giuseppina (IntechOpen, 2012)
None